2011
DOI: 10.1161/circep.111.964809
|View full text |Cite
|
Sign up to set email alerts
|

Use of an Implantable Monitor to Detect Arrhythmia Recurrences and Select Patients for Early Repeat Catheter Ablation for Atrial Fibrillation

Abstract: Background— Catheter ablation of atrial fibrillation (AF) has proved effective in curing highly symptomatic patients with paroxysmal AF. The aim of this prospective, randomized study was to identify the optimal treatment of patients with AF recurrences after the first ablation. Methods and Results— Two hundred eighty-six patients with paroxysmal AF underwent ablation (circumferential pulmonary vein isolation with linear lesions) and were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
73
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(78 citation statements)
references
References 31 publications
4
73
0
1
Order By: Relevance
“…recently for more accurate detection of AF recurrence after ablation procedures or novel pharmacological strategies. 9 As expected, the sensitivity of these diagnostic modalities is close to 100% and, as such, is much superior to that of the currently employed 24-hour HM strategies. 8,10 However, the implantation of a CM device in all patients may seem unrealistic.…”
Section: Clinical Perspectivesupporting
confidence: 53%
“…recently for more accurate detection of AF recurrence after ablation procedures or novel pharmacological strategies. 9 As expected, the sensitivity of these diagnostic modalities is close to 100% and, as such, is much superior to that of the currently employed 24-hour HM strategies. 8,10 However, the implantation of a CM device in all patients may seem unrealistic.…”
Section: Clinical Perspectivesupporting
confidence: 53%
“…[13][14][15][16]26,27 For example, PACs have previously been associated with an increased risk of incident AF in population based cohort studies. [13][14][15][16] Furthermore, Inoue et al found that ablation of PACs in addition to pulmonary vein isolation was associated with a high probability of recurrence-free survival among patients with persistent AF undergoing catheter ablation, suggesting that these electric triggers may play an important role in AF initiation.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with these aims, Pokushalov et al, 8 in this issue of Circulation: Arrhythmia and Electrophysiology, report their observations on the use of ILR to detect ERA and select patients for early repeat catheter ablation after the initial AF ablation procedure. Their study population comprised 286 patients with paroxysmal AF.…”
Section: Article See P 823mentioning
confidence: 95%